Characterization of FTIR in Graphite from Palm Oil Waste with Ferric Chloride Catalyst - Visca, Rinette; Dewi, Mubarokah Nuriaini; Liviani, Alvira; Satriawan, Bima Dwi (International Journal Labs, 2022)
Indonesia has various sources of graphite in large quantities. One of them is palm oil waste. Palm oil is a horticultural crop that acts as the largest non-oil and gas foreign exchange contributor in Indonesia. This study aims to synthesize graphite from oil palm trunks with a catalyst through the pyrolysis method. This is an experimental research which eventually generated qualitative data to be analyzed. Oil palm trunks are dried in the sun, then crushed into powder with a grinder and sieved to 200 mesh. Graphite was synthesized using a carbonization step at 500°C. Impregnation using 3M ferric chloride (FeCl3), with a concentration variation of 10% and 30%. Further activation at a temperature of 900°C for 3 hours. The results synthesis of graphite powder were washed with hydrochloric acid (HCl) and distilled water repeatedly to obtain relatively pure graphite. Graphite characterization includes Fourier Transform Infrared Spectroscopy (FTIR). The results of FTIR analysis showed that graphite contains functional groups O–H, C–H, C–O, C?C, and C=C.